Is peripheral blood cell balanced altered by the use of fresh frozen bone block allografts in lateral maxillary ridge augmentation? - Spin Neto, Rubens [UNESP]; Felipe Leite, Coletti [UNESP]; Pereira, Luis Antonio Violin Dias; Marcantonio, Elcio [UNESP]; Marcantonio Júnior, Elcio [UNESP] (Wiley, 2013)
Background: The relationship between the immune response and red and white blood cell homeostasis is cited in literature, but no studies regarding the balance of these cell populations following maxillary bone-graft surgeries can be found. Aim: The aim of this study was to evaluate the possible impairments in the blood cell balance following fresh-frozen allogeneic bone-graft augmentation procedures in patients who needed maxillary reconstruction prior to implants. Material and Methods: From 33 patients elected to onlay bone grafting procedures, 20 were treated with fresh-frozen bone allografts and 13 with autologous bone grafts. Five blood samples were collected from each patient in a 6-month period (baseline: 14, 30, 90, and 180 days postsurgery), and the hematological parameters (erythrogram, leukogram, and platelets count) were accessed. Results: All evaluated parameters were within the reference values accepted as normal, and significant differences were found for the eosinophils count when comparing the treatments (30 days, p=.035) and when comparing different periods of evaluation (allograft-treated group, baseline×180 days, p≤.05 and 90×180 days, p≤.01; autograft-treated group, 30×90 days, p≤.05 and 30×180 days, p≤.05). Conclusions: Both autologous and fresh-frozen allogeneic bone grafts did not cause any impairment in the red and white blood cell balance, based on quantitative hemogram analysis, in patients subjected to maxillary reconstruction. © 2011 Wiley Periodicals, Inc.
Keywords: Atrophic maxillae; Autologous bone graft; Blood cells; Bone allograft; Leucocytes; Lymphocytes